Environmental assessment of small-scale dairy farms with multifunctionality in mountain areas. (15th June 2016) - Salvador, Sara; Corazzin, Mirco; Piasentier, Edi; Bovolenta, Stefano
Abstract: The aim of this study was to estimate the environmental impact of organic and conventional small-scale dairy farms in mountain areas. Sixteen farms rearing the dual-purpose Rendena breed were assessed for global warming potential, acidification and eutrophication impacts through the Life Cycle Assessment method in two scenarios: the Baseline Scenario based on the actual farm data and the Milk-Beef production system Scenario assuming that calves exceeding the culling rate were fattened directly on-farm. Three different emissions allocation methods were considered: No allocation; Physical allocation, which also accounted for the co-product beef; and Economic allocation, which also accounted for the ecosystem services provided by the farms and were estimated on the basis of agri-environmental payments. Furthermore, two functional units were used: fat and protein corrected milk (FPCM) and utilizable agricultural land (UAL). Within the Baseline Scenario and with FPCM as the functional unit, performing No allocation, the mean values obtained for the global warming potential, acidification and eutrophication were 1.43 kg CO2 -eq/kg FPCM, 25.84 g SO2 -eq/kg FPCM and 3.99 g PO 4 3 − - eq / kg FPCM, respectively. The organic farms had a significantly lower eutrophication impact than the conventional farms considering all three allocation methods. Conversely, if UAL was used as the functional unit, the mean values obtained for the global warming potential, acidification and eutrophication were 0.80 kg CO2 -eq/m 2, 14.28 g SO2 -eq/m 2 and 2.32 g PO 4 3 − - eq / m 2, respectively. The Milk-Beef production system Scenario increased emissions per m 2 of UAL, but it reduced the emissions apportioned to 1 kg of FPCM, with stronger trends in the organic farms because of the increased added value of the meat production. This study highlights how strengthening beef production in dual-purpose breeds reduced the emissions apportioned to milk and suggests an approach to acknowledge multi-functionality considering some of the ecosystem services provided by the farms. Highlights: An LCA was performed on 16 small-scale dairy farms in mountain areas. Organic and conventional breeding methods were compared. Different functional units and allocation methods were applied. Environmental impact of farms changed if ecosystem services were accounted for. Considering farm multi-functionality, GWP per kg of milk was reduced.